A Nonstaining and Tasteless Hydrophobic Salt of Chlorhexidine - Menegon, Renato Farina [UNESP]; Blau, Lorena [UNESP]; Janzantti, Natalia Soares [UNESP]; Pizzolitto, Antonio Carlos [UNESP]; Correa, Marcos Antonio [UNESP]; Monteiro, Magali [UNESP]; Chin, Chung Man [UNESP] (Wiley-Blackwell, 2011)
Chlorhexidine (CHX) remains one of the most effective and widely used antiplaque agents around the world, although its side effects still limit a long-term usage as the patient compliance for oral treatment with CHX. We hypothesize that a less water-soluble tetracation salt of CHX might be able to interact weakly with tooth enamel and oral taste cells, reducing those undesirable side effects of CHX. The chlorhexidine tetrapalmitate (CHXTP) was obtained and the antimicrobial activity was evaluated by hole-plate diffusion method and twofold tube dilution method; for measurement of its propensity to stain, we used the in vitro method of polymethylmethacrylate blocks in an infusion with black tea solution; the rate of its removal from oral cavity was studied by high-performance liquid chromatography measurement of CHX extracted from human saliva samples; and its effect on the human taste perception was evaluated by taste confusion matrix method. The results showed that CHXTP salt is very active against Streptococcus mutans, with no interference on taste perception and a low tendency to stain; however, chlorhexidine digluconate shows a better retention in saliva. The use of polyvinylpyrrolidone turned possible a nonstaining and tasteless CHXTP formulation to linger in mouth. (C) 2011 Wiley-Liss, Inc. and the American Pharmacists Association J Pharm Sci 100:3130-3138, 2011
Keywords: buccal; antiinfectives; drug design; preformulation; prodrugs